2013
DOI: 10.1021/bi301510v
|View full text |Cite
|
Sign up to set email alerts
|

Identification of c-di-GMP Derivatives Resistant to an EAL Domain Phosphodiesterase

Abstract: The bacterial second messenger signaling molecule bis-(3′-5′)-cyclic dimeric guanosine monophosphate (c-di-GMP) controls important biological processes such as biofilm formation, virulence response, and motility. This second messenger is sensed by macromolecular targets inside the cell, both protein and RNA, which induce specific phenotypic responses critical for bacterial survival. One class of enzymes responsible for regulating the intracellular concentration of c-di-GMP, and therefore the physiological beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 56 publications
0
23
0
Order By: Relevance
“…Chemical analogs of cdiGMP have been developed which are able to inhibit receptor binding to cdiGMP and alter the activity of these proteins. 1316 However, many such cdiGMP analogues are not membrane permeable and therefore have limited bioactivity. High-throughput screens for allosteric inhibitors often utilize luminescent, fluorescent, or colorimetric readouts for protein binding of small molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Chemical analogs of cdiGMP have been developed which are able to inhibit receptor binding to cdiGMP and alter the activity of these proteins. 1316 However, many such cdiGMP analogues are not membrane permeable and therefore have limited bioactivity. High-throughput screens for allosteric inhibitors often utilize luminescent, fluorescent, or colorimetric readouts for protein binding of small molecules.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of these phosphodiesterases, and the absence of cdiA-or cAG-specific phosphodiesterases, could have led to the lower observed levels of cdiG in the cell lysate. The enzyme TBD1265, for instance, is a canonical EAL domain-containing phosphodiesterase that is 33-fold more selective for cdiG over cAG, with no activity toward cdiA hydrolysis (33). Furthermore, of the 28 HD-GYP and EAL proteins in V. cholera El Tor, only three HD-GYP enzymes showed cleavage activity for cAG (34).…”
mentioning
confidence: 99%
“…We have previously demonstrated that dithiophosphate analogs of c-di-GMP are resistant to enzymatic degradation by EAL domain proteins. 66 . Together, these data suggest that replacing both of the phosphodiester bonds with phosphorothioate linkages results in a PDE-resistant analog.…”
Section: Resultsmentioning
confidence: 99%